Hotel Services Outsourcing in Public Entities of Health Care Sector - Lewandowska, Hanna (Polish Journal of Public Health, 2009)
Limited amount of financial means directed to Independent  Public Healthcare Centres (SPZOZ) by the major beneficiary i.e. the National Health Fund, resulting from contracts concluded for medical services provision, and, still rising non-medical costs make entities of health care sector search for solutions that will cut down their operational costs. Outsourcing is one of the means that could be helpful here, i.e. using services of external entities that are able to meet requirements of the ordering party. Concluding medical service contracts (laboratory and diagnostic examination) and non-medical service contracts resulted in creating a model of an open management based on outsourcing of services. Leading to cost reduction and changes of their structure (from fixed into the changeable costs), outsourcing became a management model facilitating processes (of patient’s hospitalisation) and restructuring processes. Separating processes/divisions facilitating the process of medical healthcare services provision from the organizational entity structure leads to lean management. It allows the managers to focus on processes directly connected with operational activity of the entity.A crucial tool facilitating the above mentioned activities is the public procurement market, which can guarantee an objective price; it also allows to choose the best possible bidder resulting from market mechanisms. However, the determinants are the requirements of Independent Public Healthcare Centres contained in the Specification of Essential Terms of Procurement (SIWZ), which significantly affect the number of entities interested in providing services  for the health sector entities. So-called hotel services (catering, laundry services and cleaning/maintenance services) are most often commissioned to specialized external entities; because of their simple administrative character they may be separated from the organizational structure of the company. Conditions addressed to a contractor applied by Independent Public Healthcare Centres contained in the Specification of Essential Terms of Procurement in the form of, inter alia, criteria for tenders evaluation results, have an impact on outsourcers’ interest in these services